Identification of Vocational High School Competency Based on Leading Potential of The Region in Batu City - Prabowo, Tito Tri (Fakultas Teknik Universitas Negeri Malang, 2021)
The target of the synchronization program are schools that have areas of expertise that are not in accordance with the potential of the superior map of the region, the difference is seen from the superior potential of the region synchronized with the distribution of areas of expertise in each province in Indonesia. This research aims to determine the competence of vocational skills in Batu City, based on the findings of the phenomenon of various regional potentials owned by each sub-district spread across Batu City with a Spectrum of Middle School Expertise Vocational High School (SMK) / Vocational Madrasah Aliyah (MAK), with the hope that graduates who are intended to be able to develop and cultivate the potential of the region properly. This type of research used qualitative descriptive, data collection methods conducted by interview, study of related documents, and observation of findings in the field to collect any data and facts scattered throughout the region sub-districts in Batu City (Kecamatan Batu, Bumiaji, Junrejo), as well as with data triangulation analysis techniques. Based on the findings in Batu District, there are 3 main potentials, namely the tourism sector, th e restaurant sector, and the tourism sector transportation and agriculture. Batu District has 4 main labour sector priorities, namely the restaurant, hotel sector, tourism and transportation service sector, and agriculture sector. Sync result Finding the potential of the Batu City area with a spectrum of vocational expertise competencies is expected to create competent human resources in developing the Batu City area.